Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Emission of fine and ultrafine nanoparticle aerosols from composites functionalized with Multi-Wall Carbon Nano Tubes (MWCNTs) subjected to sliding wear: the influence of matrix material - Francisca Husanu; Juan Camilo Vélez Molina; Jesús Antonio Carlos Cornelio; Juan Felipe Santa Marín; Alejandro Toro; Marta Castellote; Roman Nevshupa (ENGINEERING Environment, 2026)
While multi-wall carbon nanotube (MWCNT)-reinforced nanocomposites offer improved wear resistance, the health implications of released nanoparticle aerosols are a concern. This research aimed to understand the influence of matrix material on the tribological properties, microstructure, and triboemission of MWCNT-functionalized polymer and cement composites. Key findings reveal that aerosol emission cannot be predicted solely based on porosity and mechanical properties. The observed variations in MWCNT effects across different matrix materials are attributed to the distinct dominant wear mechanisms in each.

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Biomass characterization and solvent extraction as tools to promote phenol production from urban pruning - Fabiola Valdebenito; Rodrigo Ramírez-Álvarez; M. Alexandra Muñoz; Gina Pecchi; Roberto Canales; Sebastián Ormazabal; Robinson Muñoz; Serguei Alejandro-Martín; Franck Quero; Roman Adam; Gerald Cifuentes; J. Flavio Espinoza-Monje; et al. (Fuel, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Spent coffee grounds as feedstock for the production of biosurfactants and the improved recovery of melanoidins - Ignacio Moya-Ramírez; María Encarnación Pegalajar-Robles; Michele Debiasi Alberton; José A. Rufián-Henares; Alejandro Fernández-Arteaga; Miguel Garcia-Roman; Deisi Altmajer-Vaz (World Journal of Microbiology and Biotechnology, 2023)
Spent coffee grounds (SCG) are wastes generated in high amounts worldwide. Their composition makes them a promising feedstock for biotechnological processes. Here we show that the production of the biosurfactant surfactin by submerged culture of a Bacillus subtilis strain growing on SCG is possible, reaching concentrations up to 8.8 mg/L when using SCG at 8.3 g/L in the medium. In addition, we report a synergy between the production of surfactin and the recovery of melanoidins, an added-value compound already present in SCG. More specifically, the concentration of melanoidins in the culture medium increased between 2.1 and 2.5 times thanks to the presence of the B. subtilis in the culture. Furthermore, we have observed a strong interaction between surfactin and melanoidin aggregates through dynamic light scattering measurements, and that both of them can be co-purified with an acid precipitation. We have also characterized the interfacial and antioxidant properties of the cell-free supernatant and surfactin extract, as well as the distribution of the congeners of the biosurfactant. Altogether, this work describes a promising approach to obtain biosurfactants and antioxidant molecules in a single operation, which can be used to design several new formulations of interest for bioremediation, amendment of soils, food and cosmetics.

Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords - Nadescha Zwerschke; Chester J. Sands; Alejandro Roman‐Gonzalez; David K. A. Barnes; Alice Guzzi; Stuart Jenkins; Carlos Muñoz‐Ramírez; James Scourse (Global Change Biology, 2022)
Global warming is causing significant losses of marine ice around the polar regions. In Antarctica, the retreat of tidewater glaciers is opening up novel, low‐energy habitats (fjords) that have the potential to provide a negative feedback loop to climate change. These fjords are being colonized by organisms on and within the sediment and act as a sink for particulate matter. So far, blue carbon potential in Antarctic habitats has mainly been estimated using epifaunal megazoobenthos (although some studies have also considered macrozoobenthos). We investigated two further pathways of carbon storage and potential sequestration by measuring the concentration of carbon of infaunal macrozoobenthos and total organic carbon (TOC) deposited in the sediment. We took samples along a temporal gradient since time of last glacier ice cover (1–1000 years) at three fjords along the West Antarctic Peninsula. We tested the hypothesis that seabed carbon standing stock would be mainly driven by time since last glacier covered. However, results showed this to be much more complex. Infauna were highly variable over this temporal gradient and showed similar total mass of carbon standing stock per m 2 as literature estimates of Antarctic epifauna. TOC mass in the sediment, however, was an order of magnitude greater than stocks of infaunal and epifaunal carbon and increased with time since last ice cover. Thus, blue carbon stocks and recent gains around Antarctica are likely much higher than previously estimated as is their negative feedback on climate change.

Sclerochronology in the Southern Ocean - Alejandro Roman Gonzalez (Polar Biology, 2021)
This manuscript aims to provide a comprehensive review of the work done by Antarctic sclerochronology research across different taxa (arthropods, bivalves, brachiopods, bryozoans, cephalopods, hard and soft corals, gastropods, echinoderms and teleost fish), provide an analysis of current challenges in the discipline and start a discussion of what sclerochronology can offer for Antarctic research in future. The Southern Ocean ecosystem remains largely unstudied in part for its remoteness, extreme climate and strong seasonality. This lack of knowledge, some of it even on basic biological information, it is especially worrying due to ongoing climate-driven changes that the Southern Ocean ecosystem is experiencing. Lack of long-term in situ instrumental series has also being a detriment to understand long-term feedbacks between the physical environment and the ecosystem. Sclerochronology, the study of periodic accretional patterns in the hard body structures of living organisms, has contributed to a wide range of Antarctic research disciplines (e.g. paleoclimate reconstructions, population structure analysis, environmental proxies). This review highlights a disparity in research focus by taxa with some groups (e.g. bivalves, teleost fish) attracting most of the research attention, whereas other groups (e.g. gastropod) have attracted much little research attention or in some cases it is almost non-existent (e.g. echinoderms). Some of the long-lived species considered in this review have the potential to provide the much-needed high-resolution eco-environmental proxy data and play an important role in blue carbon storage in the Sothern Ocean. Another issue identified was the lack of cross-validation between analytical techniques. Graphic abstract

Blue carbon gains from glacial retreat along Antarctic fjords: What should we expect? - David K. A. Barnes; Chester J. Sands; Alison Cook; Floyd Howard; Alejandro Roman Gonzalez; Carlos Muñoz–Ramirez; Kate Retallick; James Scourse; Katrien Van Landeghem; Nadescha Zwerschke (Global Change Biology, 2020)
Rising atmospheric CO 2 is intensifying climate change but it is also driving global and particularly polar greening. However, most blue carbon sinks (that held by marine organisms) are shrinking, which is important as these are hotspots of genuine carbon sequestration. Polar blue carbon increases with losses of marine ice over high latitude continental shelf areas. Marine ice (sea ice, ice shelf and glacier retreat) losses generate a valuable negative feedback on climate change. Blue carbon change with sea ice and ice shelf losses has been estimated, but not how blue carbon responds to glacier retreat along fjords. We derive a testable estimate of glacier retreat driven blue carbon gains by investigating three fjords in the West Antarctic Peninsula (WAP). We started by multiplying ~40 year mean glacier retreat rates by the number of retreating WAP fjords and their time of exposure. We multiplied this area by regional zoobenthic carbon means from existing datasets to suggest that WAP fjords generate 3,130 tonnes of new zoobenthic carbon per year (t zC/year) and sequester >780 t zC/year. We tested this by capture and analysis of 204 high resolution seabed images along emerging WAP fjords. Biota within these images were identified to density per 13 functional groups. Mean stored carbon per individual was assigned from literature values to give a stored zoobenthic Carbon per area, which was multiplied up by area of fjord exposed over time, which increased the estimate to 4,536 t zC/year. The purpose of this study was to establish a testable estimate of blue carbon change caused by glacier retreat along Antarctic fjords and thus to establish its relative importance compared to polar and other carbon sinks.

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Giovanni Di Virgilio; Jason P. Evans; Alejandro Di Luca; Roman Olson; Daniel Argüeso; Jatin Kala; Julia Andrys; Peter Hoffmann; Jack J. Katzfey; Burkhardt Rockel (Climate Dynamics, 2019)

Projected change in characteristics of near surface temperature inversions for southeast Australia - Fei Ji; Jason Peter Evans; Alejandro Di Luca; Ningbo Jiang; Roman Olson; Lluis Fita; Daniel Argüeso; Lisa T.-C. Chang; Yvonne Scorgie; Matt Riley (Climate Dynamics, 2019)

The fishery of the striped venus Chamelea gallina (Linnaeus, 1758) in the Spanish waters of the Gulf of Cadiz (SW Spain): distribution and abundance of target and commercial discarded species. - Miguel Cojan Burgos; Luis Silva Caparro; Ana Rodriguez-Rua Franch; Raimundo Blanco Pérez; Sara Roman Moreno; Esperanza Garcia Sumariva; Alejandro Garcia Gomez; MarinaL Delgado Fernández; Alejandro Terron Singler; Javier Collado Vallejo; Rafael Gálvez César; Francisco Morales Mazo (Frontiers in Marine Science, 2019)

Metastatic sympathetic paraganglioma in a patient with loss of the SDHC gene - Thereasa Rich; Michelle Jackson; Alejandro Roman-Gonzalez; Komal Shah; Gilbert J. Cote; Camilo Jimenez (Familial Cancer, 2015)

Modelling the Competitive Sorption Process of Multiple Solutes During their Transport in Porous Media - Manuel Alejandro Salaices Avila; Roman Breiter (Environmental Modeling & Assessment, 2009)